2011
DOI: 10.1002/sia.3864
|View full text |Cite
|
Sign up to set email alerts
|

In situ TEM study on the improvement of contact resistance between a carbon nanotube and metal electrodes by local melting

Abstract: Contact resistance between a multiwalled carbon nanotube (MWNT) and a metal electrode is governed by the contact structure. The relationship between the contact structure and electrical resistance was examined by in situ transmission electron microscopy using a nickel electrode and MWNTs with two kinds of tip structure; close-capped and open-ended. When the current density through the contact region reached a threshold value about 7.6 Â 10 8 A/cm 2 , the MWNT tip was embedded below the nickel surface by local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…From our previous study related to electric conductive properties of an Au–MWNT–Ni system, R Au + R CNT‐out in Eqs can be estimated to be ca. 5 kΩ.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From our previous study related to electric conductive properties of an Au–MWNT–Ni system, R Au + R CNT‐out in Eqs can be estimated to be ca. 5 kΩ.…”
Section: Resultsmentioning
confidence: 99%
“…They revealed that Joule heating by high current flow brought about fusion of a metal (W) electrode and formation of tungsten carbide, leading to a reduction of contact resistance. Karita et al . also reported structural change of the CNT/metal [gold (Au) and nickel (Ni)] interface and the corresponding reduction of contact resistance during the passage of electric current by in situ TEM.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a microscope operating at 120 kV, two metals were studied, namely, Ni and Au, along with arc-made MWCNTs with two different types of tips, open and closed. Current densities in the order of 10 8 A/cm 2 were reportedly needed to induce melting of the Ni surface at the contact region [ 87 ]. This annealing process led to a marked decrease of the overall electrical resistance, particularly for the open-end nanotubes.…”
Section: Carbon Nanotubesmentioning
confidence: 99%